2018
DOI: 10.1111/are.13813
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of free-floating and emergent aquatic macrophytes in constructed wetlands for the treatment of a fishpond effluent

Abstract: Many studies have evaluated the efficiency of constructed wetlands (CWs) for the treatment of fishpond effluents, but only a few have compared between CWs with emergent and free-floating macrophytes and assessed the amount of nutrients removed only by the macrophytes. For this purpose, we performed an experiment during 113 days in which we treated a fishpond effluent using four different CWs:(i) with the free-floating macrophyte Eichhornia crassipes (Ec); (ii) without E. crassipes (WEc); (iii) with a substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
(52 reference statements)
0
16
0
1
Order By: Relevance
“…Consequently, the efficiency of the wetland system in phytoremediation and/or the competence of the macrophytes can be affected by different climatic conditions, soil type or aquatic biodiversity [25]. Both natural and constructed wetlands are worldwide considered as a cost-effective and an alternative technology for polluted water and wastewater treatment, they have been increasingly used to successfully remove pollutants from domestic and industrial effluents [11,14,26,27]. Macrophytes used in phytoremediation in CW systems can diverge to various types based on their adaptations to life in water.…”
Section: Natural and Constructed Wetlands In Phytoremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the efficiency of the wetland system in phytoremediation and/or the competence of the macrophytes can be affected by different climatic conditions, soil type or aquatic biodiversity [25]. Both natural and constructed wetlands are worldwide considered as a cost-effective and an alternative technology for polluted water and wastewater treatment, they have been increasingly used to successfully remove pollutants from domestic and industrial effluents [11,14,26,27]. Macrophytes used in phytoremediation in CW systems can diverge to various types based on their adaptations to life in water.…”
Section: Natural and Constructed Wetlands In Phytoremediationmentioning
confidence: 99%
“…Floating plants include free floating and floating-leaved plants such as Eichhornia crassipes, Lemna sp, and Azolla sp. [24,27,29]. Wetland plants can take up heavy metals and nutrients through root systems and accumulate them in the biomass reducing therefore the concentrations of these polluting elements.…”
Section: Macrophytes For Phytoremediationmentioning
confidence: 99%
“…Different studies have demonstrated that managed cattail in constructed wetlands could provide bene cial ecosystem services (6,7) and sustainable biomass for biofuel feedstocks (13,14) and bioproducts (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although considered an invasive plant, cattail provides different raw materials (weaving) and serves as food for humans and livestock (rhizomes). In recent years, cattail has been used in wastewater treatments and industrial-site remediation due to its great capacity to remove particle matter, nutrients and metals from eutrophic waters (6)(7)(8). For wastewater treatment, this species has been used to form green filters that use different types of biological elements (plants and microorganisms).…”
Section: Introductionmentioning
confidence: 99%